2020
DOI: 10.1177/1526602820943857
|View full text |Cite
|
Sign up to set email alerts
|

Floating Stent-Graft as a Support to Bridge an Unfavorable Renal Artery During Postdissection TAAA Repair Using a Multibranched Thoracoabdominal Endograft

Abstract: Purpose: To report an unusual endovascular technique to manage unfavorable renal artery anatomy encountered in an urgent case of symptomatic postdissection thoracoabdominal aortic aneurysm (TAAA) treated with an off-the-shelf multibranched device. Technique: The technique is demonstrated in a 77-year-old woman who had a history of previous open abdominal aortic aneurysm repair and an emergent procedure to implant a thoracic endograft and an aortic bare Z-stent (PETTICOAT) for acute Stanford type B dissection 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In the December 2020 issue of the JEVT , Rossi et al 6 describe a novel bailout technique they found useful in a postdissection TAAA case when a t-Branch implantation was hampered by bare stents from a PETTICOAT technique used during a prior thoracic endovascular aortic repair (TEVAR). Despite several attempts the tortuous left renal artery could not be cannulated so the authors suspended a Viabahn stent-graft in the cul-de-sac not connected to either the branch or the renal artery but held distally by the struts of the bare stent as well as by the relatively small aneurysm sac.…”
mentioning
confidence: 99%
“…In the December 2020 issue of the JEVT , Rossi et al 6 describe a novel bailout technique they found useful in a postdissection TAAA case when a t-Branch implantation was hampered by bare stents from a PETTICOAT technique used during a prior thoracic endovascular aortic repair (TEVAR). Despite several attempts the tortuous left renal artery could not be cannulated so the authors suspended a Viabahn stent-graft in the cul-de-sac not connected to either the branch or the renal artery but held distally by the struts of the bare stent as well as by the relatively small aneurysm sac.…”
mentioning
confidence: 99%